Huge Pseudoaneurysm of the Femoral Artery after Internal Fixation of Femoral Trochanteric Fracture - Hideyuki Kinoshita; Masayuki Hashimoto; Jiro Hirayama; Kouji Fujita; Yoshio Takeuchi; Junichi Iwasaki; Hironori Yamasaki; Mitsuhiro Kitamura; Seiji Ohtori; Tsuguo Morikawa (Case Reports in Orthopedics)
Pseudoaneurysm is one of the most serious complications of femoral trochanteric fracture surgery. Since the rupture of pseudoaneurysm may lead to death, early detection is important. We report the case of an 80-year-old male who developed pain in the proximal thigh and severe swelling after internal fixation of a femoral trochanteric fracture with a hip nail. Angiography revealed a pseudoaneurysm of a branch of the deep femoral artery near the interlocking screw. The vascular lesion was immediately treated by transcatheter embolization, and the vascular leakage was completely resolved with catheter embolization. After embolization, the patient’s clinical state improved rapidly, and the laboratory values improved to normal after several weeks. The current case study reminds us that pseudoaneurysm can occur after intramedullary nail placement to treat a femoral trochanteric fracture.